Studi Daur Ulang Sampah Kertas dari Sumber Institusi di Kota Padang - Rizki Aziz; Silvia Nitri (Universitas Andalas, 2018)
Based on Onesta (2004) research, paper waste is the second largest waste component of Padang City's institutional waste, which is 23% after 52% of food waste. Paper comes from wood fiber which is a material that can be recycled, maximizing the potential for recycling will be able to increase efforts to preserve the environment and reduce environmental impacts. To assess the potential utilization of paper waste as recycled material, a study of the potential of paper waste recycling from institutions in the city of Padang is carried out through determining generation and composition. This research was conducted in August by taking a sample of 21 institutions (10 offices, 10 schools and 1 hospital) in accordance with SNI 19-3964-1994. From the research, it was obtained that the average waste generation of paper from institutional sources in Padang City was 0.048 l / m2 / hr where the waste generation of paper from office sources was 0.047 l / m2 / hr, school 0.059 l / m2 / h and hospitals 0.037 l / m2 / hr. For the composition of paper waste includes archival paper 44.73%, mixed paper 8.83%, cardboard and carton boxes 14.65%, 5.26% cardboard, 5.39% newspaper paper, 2.22% art paper, tissue 5.08%, carbon paper 0.15%, food wrappers 9.15% and others 4.55%. The potential of paper waste recycling is 78.88%, while that of not paper is 21.16%. To optimize the potential for paper recycling, it is recommended to separate paper waste from the source.